A novel method for isolation new strain of E. coli ( resist for Ampicillin and sensitive for Gentamycin ) and other (sensitive for Ampicillin and resist for Gentamycin )and check it's conjugation by solid media , liquid media and it's stability by serial - Mohammed Abdul Rahmman Mohammed, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
Bacterial strains ( E. coli ) were collected from two different places , The first strain was collected from central Laboratory – Baghdad university , meanwhile the second strain was collected from pathogenic laboratory – Baghdad universityReplica plating and gradient plate method technique were used to prepare strains with different multi trailsReplica plating was used to select strain resist to specific antibiotic with low concentration ( sensitive for other type of antibiotic ) then go head subsequently with gradient plate method to adapt the strain to resist (high concentration )Replica plating was used to select first strain resist to Amp. ( 100 Mg / ml ) and ( sensitive to Gen.) then gradient plate method was used to adapt first strain to resist Amp. (500 Mg-ml ) therefore. first strain was resistant to Amp. ( 500 Mg / ml ) and sensitive to Gen. (500 Mg / ml ) , on other hand ,by using same methods , second strain was resistant to Gen. ( 500 Mg / ml ) and sensitive to Amp.. (500 Mg / ml )To visualize if ( Amp. resist trail and Gen. resist trail ) carried on plasmid , first and second strains were conjugated by using conjugation technique in solid media and liquid media .The conjugant strain was resistant to ( 1000 Mg / ml ) by which it resists Amp. and Gen. , (500 Mg / ml ) for each antibiotic .The efficiency of conjugant was determined on solid media and liquid media , it was so high a round 9% . The conjugant strain was checked for stability of it's plasmid by using sub – culturing method . It was stable for 25 times of sub-culturingConcentration of the protein for E. coli ( resist for Ampicillin and sensitive for Gentamycin ) and other strain E. coli (sensitive for Ampicillin and resist for Gentamycin ) was 0.0021and 0.0052 meanwhile conjugant was 0.106Finally , . using replica plating , gradient plate and conjugation process consider as a novel technique to prepare strains with multi trails which resist very high concentration of antibiotics and efficient conjugation process